GaN-based Schottky barrier ultraviolet photodetectors with graded doping on patterned sapphire substrates. (July 2017) - Mou, Wenjie; Zhao, Linna; Chen, Leilei; Yan, Dawei; Ma, Huarong; Yang, Guofeng; Gu, Xiaofeng
Highlights: Extremely low dark current density and high UV-to-visible light rejection ratio. Low response time and good electrical and thermal reliability. High specific detectivity. Abstract: In this paper, we demonstrate high performance GaN-based Schottky-barrier ultraviolet (UV) photodetectors with graded doping prepared on patterned sapphire substrates. The fabricated devices exhibit an extremely low dark current density of ∼1.3 × 10 −8 A/cm 2 under −5 V bias, a large UV-to-visible light rejection ratio of ∼4.2 × 10 3, and a peak external quantum efficiency of ∼50.7% at zero bias. Even in the deeper 250–360 nm range, the average external quantum efficiency still remains ∼40%. From the transient response characteristics, the average rising and falling time constants are estimated ∼115 μs and 120 μs, respectively, showing a good electrical and thermal reliability. The specific detectivities D ∗, limited by the thermal equilibrium noise and the low-frequency 1/ f noise, are derived ∼5.5 × 10 13 cm Hz 1/2 /W (at 0 V) and ∼2.68 × 10 10 cm Hz 1/2 W −1 (at −5 V), respectively.